An improved double diffusion analysis of non-Newtonian chemically reactive fluid in frames of variables properties - Waqas, M.; Khan, W.A.; Asghar, Z. (International communications in heat and mass transfer, 2020)
Stretching flows subject to heat/mass transference have implication in contemporary research era and industry because of their diverse demands in chemical systems and engineering. Such demands encompass filaments, paper fabrication, glass fiber and polymer sheets. Owing to such prospective demands, we interpreted the Jeffrey liquid reactive flow under non-linear convection. We scrutinized the transference of heat/mass under generalized Fourier-Fick relations. Thermal conductivity depends on temperature while mass diffusivity is dependent on concentration. Besides, heat source along with first-order chemical reaction aspects are accounted. Relevant transformations are exerted to achieve non-linear differential systems which are solved through homotopy scheme. Influences of significant factors are exhibited via graphical benchmark.